Analysis of Grade 7 Students' Interest in Learning Mathematics Using Geogebra Learning Media on Geometry Transformation Material - Ramadhani, Zahra (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research was conducted to analyze interest in learning in grade 7 junior high school students when learning with geogebra media on geometric transformation material. The method used in this research is descriptive. The population of this research were students at SMPN 1 Kisaran, taking a sample of 30 students from class 7 Kisaran. The instrument used is a non-test instrument in the form of a questionnaire about students' interest in learning after learning using Geogebra media which consists of 20 statements. The results of the analysis in this research received a positive response to interest in learning mathematics with Geogebra media. This can be seen from the percentage value of each indicator which shows that the majority of students have an interest in learning mathematics using Geogebra media.